Characteristics of serum bile acid profiles among individuals with metabolic dysfunction-associated steatotic liver disease - Sheng Lyu; Jiani Yang; Xin Xin; Qinmei Sun; Beiyu Cai; Xin Wang; Ziming An; Jian Sun; Yiyang Hu; Lei Shi; Qin Feng; Xiaojun Gou (BMC Gastroenterology)
Abstract Background Metabolic dysfunction-associated steatotic liver disease (MASLD) has become the predominant chronic liver condition globally. Bile acid (BA) metabolism contributes significantly to MASLD progression. In this multicenter clinical study, we aimed to characterize serum BA profiles in patients with MASLD and identify specific alterations compared to healthy controls. Methods All MASLD cases were sourced from the gastroenterology outpatient departments of Shanghai Baoshan Hospital of Integrated Chinese and Western Medicine, Shanghai Baoshan District Songnan Community Health Service Center, and Lianyungang Oriental Hospital between June 2015 and December 2019. The data were analyzed using SPSS version 26.0, with a p-value of less than 0.05 considered significant. Results A total of 215 participants (35.3% women) with MASLD and 49 controls (44.9% women), aged 18–65 years, were included. MASLD patients showed higher levels of serum total BA (TBA), cholic acid (CA), chenodeoxycholic acid (CDCA), and ursodeoxycholic acid (UDCA) (p < 0.05, p < 0.01) when compared to controls. Furthermore, women patients with MASLD demonstrated notably higher levels of lithocholic acid (LCA), glycolithocholic acid (GLCA), and taurolithocholic acid (TLCA) than men patients with MASLD (p < 0.025, p < 0.01). Compared to women, men exhibited a higher proportion of primary to secondary BAs. Additionally, in men patients with MASLD, the serum concentrations of CA, CDCA, glycocholic acid (GCA), glycochenodeoxycholic acid (GCDCA), and taurochenodeoxycholic acid (TCDCA) exhibited significant negative correlations with ALT levels, while deoxycholic acid (DCA) and TLCA showed negative correlations with BMI. Conclusions Patients with MASLD exhibited notable variations in BA profiles, including sex-specific differences. This study provides corresponding evidence on the association between BAs and MASLD. Trial registration Chinese Clinical Trial Registry, NO: ChiCTR-OOC-15006157, registration date: March 25, 2015.